Effectiveness of using interest rate futures contracts in hedging 90-day treasury bill and bank bill. - Lee, Boon Ai. (2008)
This project investigates the effectiveness of using interest rate futures contracts in hedging short-term securities, namely 90-day treasury bill and 90-day bank bill.